2001
DOI: 10.1002/ajmg.10029
|View full text |Cite
|
Sign up to set email alerts
|

Subtelomeric rearrangements detected in patients with idiopathic mental retardation

Abstract: A screening for submicroscopic rearrangements was performed in 111 patients with idiopathic mental retardation (MR) using fluorescence in situ hybridization (FISH) probes from the subtelomeric regions of all chromosome arms. Ten cryptic rearrangements were found (9%): five de novo deletions; one unbalanced de novo translocation; three unbalanced inherited translocations; and one unbalanced recombinant chromosome, inherited from a parent with a pericentric inversion. In addition, 50 of the patients were screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(127 citation statements)
references
References 27 publications
(18 reference statements)
5
118
1
3
Order By: Relevance
“…19,[23][24][25]27 When all the data are considered, the average prevalence of the 2qtel deletion is approximately 5%. In our study, 6% of the patients had the 2qtel deletion, and segregation analysis of the 2qtel deletion in relevant family members showed no correlation with mental retardation and other phenotypic anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…19,[23][24][25]27 When all the data are considered, the average prevalence of the 2qtel deletion is approximately 5%. In our study, 6% of the patients had the 2qtel deletion, and segregation analysis of the 2qtel deletion in relevant family members showed no correlation with mental retardation and other phenotypic anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…The mother was a carrier of the balanced t(9;13). Rossi et al 12 reported a de novo 9qter deletion in a moderately mentally retarded child with facial dysmorphism (not further specified), and also Anderlid et al 32 in a 25 year old severely mentally retarded woman with epilepsy, synophrys, hypertelorism, and strabismus, and Rio et al 14 in a severely mentally retarded female with obesity, abnormal genitalia, and hyperactivity.…”
Section: Qmentioning
confidence: 95%
“…A der(2)t(2;7)(q73;q36) was detected in a severely cognitively retarded 3 year old boy with facial dysmorphism (prominent forehead, downward slanting palpebral fissures, arched eyebrows, long eyelashes, small mouth with short philtrum and thin upper lip), a few café au lait spots, pectus carinatum, and talipes equinovarus. 30 Mildly mentally retarded patients with 2qter deletions and an inconsistent clinical phenotype have been reported [31][32][33] and Figure 1 Clinical photographs of various patients with subtelomere deletions.…”
Section: Qmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies used fluorescence in situ hybridization (FISH) of subtelomeric probes to detect chromosomal rearrangements [68][69][70]72,[74][75][76][77][78] and two studies used microsatellite markers. 71,73 The latter approach is able to detect uniparental disomy (inheritance of both copies of one chromosome from the same parent).…”
mentioning
confidence: 99%